Genome-wide microhomologies enable precise template-free editing of biologically relevant deletion mutations - Janin Grajcarek (Nature Portfolio, 2019)
DNA repair by microhomology-mediated end joining creates precise deletions based on flanking microhomologies. Here the authors use CRISPR-Cas9 to recreate pathogenic deletion mutations using existing microhomologies in the human genome identified by their program MHcut.